2015
DOI: 10.3174/ajnr.a4551
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Intravenous Tirofiban as Antiplatelet Premedication for Stent-Assisted Coiling in Acutely Ruptured Intracranial Aneurysms

Abstract: BACKGROUND AND PURPOSE: Stent-assisted coiling of intracranial aneurysms requires antiplatelet therapy, typically aspirin and clopidogrel to prevent thromboembolic complications. There is a substantial concern that tirofiban may increase the risk of hemorrhage when used as an antiplatelet premedication in ruptured intracranial aneurysms. Our aim was to evaluate the safety and efficacy of intravenous tirofiban administration, instead of oral dual antiplatelet agents, as an antiplatelet premedication for stent-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 31 publications
(27 reference statements)
3
30
0
Order By: Relevance
“…Our results also showed a trend toward increased risk of thrombus formation during stent-assisted coiling, probably because of insufficient use of antiplatelet therapy in the early stage of subarachnoid hemorrhage or resistance to antiplatelet therapy 24. Kim et al 25 suggested that use of intravenous tirofiban may be an effective approach during stent-assisted coiling of ruptured aneurysms. However, intravenous tirofiban or abciximab before stent placement was not used in our patients because the safety of these drugs was unclear during our study.…”
Section: Discussionsupporting
confidence: 51%
“…Our results also showed a trend toward increased risk of thrombus formation during stent-assisted coiling, probably because of insufficient use of antiplatelet therapy in the early stage of subarachnoid hemorrhage or resistance to antiplatelet therapy 24. Kim et al 25 suggested that use of intravenous tirofiban may be an effective approach during stent-assisted coiling of ruptured aneurysms. However, intravenous tirofiban or abciximab before stent placement was not used in our patients because the safety of these drugs was unclear during our study.…”
Section: Discussionsupporting
confidence: 51%
“…Higher doses are required if a thrombotic stent occlusion has already occurred. Tirofiban has also been used for this purpose [ 16 ] and with similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Another small series reported on the use of tirofiban for SAC of acutely ruptured intracranial aneurysms. Kim et al treated 41 patients with SAC and intravenous tirofiban: 0.4 µg/kg/min bolus for 30 min, followed by 0.10 µg/kg/min maintenance infusion 26. Intravenous heparin was administered (5000 U/1000 mL of 0.9% normal saline) as a maintenance infusion through the guide catheter, but no bolus was infused.…”
Section: Discussionmentioning
confidence: 99%